2011
DOI: 10.1155/2011/530728
|View full text |Cite
|
Sign up to set email alerts
|

Measuring and Modeling of P- and S-Wave Velocities on Crustal Rocks: A Key for the Interpretation of Seismic Reflection and Refraction Data

Abstract: Lithologic interpretations of the earth crust from seismic wave velocities are non-unique so that inferences about composition can not be drawn. In order to evaluate how elastic properties of rock materials are controlled by lithology at in situ pressures and temperatures, compressional (Vp), shear wave velocities (Vs) and velocity anisotropy of crustal rocks were measured at conditions of greater depth. The first part deals with the interdependence of elastic wave propagation and the physical and lithological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 22 publications
2
6
0
Order By: Relevance
“…The pressure derivative (in the range P = 0.3 to 0.6 GPa) was then used to linearly extrapolate the velocity data, which yielded a Vp value of 6.04 km s −1 under ambient conditions. This is the so-called intrinsic velocity of Kern (2011). As in previous studies (Shingai et al 2001;Kitamura et al 2003;Kono et al 2004;Nishimoto et al 2005;Ishikawa et al 2008), linear trends of velocity as a function of pressure were observed above a threshold pressure of between 0.3 and 0.6 GPa.…”
Section: Resultssupporting
confidence: 71%
“…The pressure derivative (in the range P = 0.3 to 0.6 GPa) was then used to linearly extrapolate the velocity data, which yielded a Vp value of 6.04 km s −1 under ambient conditions. This is the so-called intrinsic velocity of Kern (2011). As in previous studies (Shingai et al 2001;Kitamura et al 2003;Kono et al 2004;Nishimoto et al 2005;Ishikawa et al 2008), linear trends of velocity as a function of pressure were observed above a threshold pressure of between 0.3 and 0.6 GPa.…”
Section: Resultssupporting
confidence: 71%
“…The Poisson's ratios, , in Table 1 are similar to those reported in seismic studies-both laboratory and field based-of continental lithologies (Christensen, 1996;Holbrook et al, 1999;Kern, 2011;Lombardi et al, 2008;Miller & Christensen, 1994). However, the shallow to midcrustal depth V p ∕V s ratios we calculate are consistently higher than the V p ∕V s ( values, from the h-method of Zhu & Kanamori, 2000) determined by Stanciu et al (2016) for the IDOR area.…”
Section: Damping Bias Shear Velocities V P ∕V S and Poisson's Ratiosupporting
confidence: 83%
“…Fountain et al, 1994;Ji et al, 1997). In addition to poor lateral resolution, the detection of heterogeneities in the lower crust may be difficult due to the non-unique lithological interpretation of lower crustal rocks from seismic velocities since a variety of rock type mixtures can yield the same velocities (Kuusisto et al, 2006;Kern, 2011). Additional constraints can be established if the seismic data are correlated with experimentally determined or calculated P-and S-wave velocities at lower crustal conditions for rock samples collected from surface outcrops or from xenoliths (Christensen and Wepfer, 1989;Jackson et al, 1990;Kern et al, 1999;Kuusisto et al, 2006;Kern, 2011).…”
Section: Introductionmentioning
confidence: 99%